Multiport Multiband Decoupling Optimization for Miniature Antennas - Serrano, Raquel; Capdevila, Santiago; Aguasca, Albert; Romeu, Jordi; Jofre, Lluis (Společnost pro radioelektronické inženýrství, 2009)
Multiband multiport antennas are increasingly used for wireless communications and sensing miniature devices. The equations governing the multiport multiband antennas are analyzed in this paper with the objective of drawing the design guidelines for low coupling small antennas. Those guidelines have been applied in the design and optimization of a two-port dual band small antenna of size around λ0/13 x λ0/13 at the lowest frequency. Certain coupling conditions are applied to the port loads achieving a coupling reduction of 8 dB when having a simple two-element real load. A reduction of 27 dB can be obtained when having ideal loads composed by a higher number of elements. The antenna geometry is shown together with coupling minimization results.
Keywords: Multiport multiband antennas; miniature antennas; decoupling; S-parameters; efficiency